الاجتهاد في العلة عند الإمام الغزالي - ت٤مد ياستُ خينش; دأ.د عيد الرتٛاف مايدم/ (جامعة عمار ثليجي الاغواط, 2023)
104 كعاؼ الأعلب ات١تًجم ت٢م ...................................................... 92 قائمة ات١صادر كات١راجع ........................................................... 94 فهرس ات١وضوعات .............................................................. 99 ملخص الرسالة ................................................................. 104 105 ملخص المذكرة: يناقش ىذا اليحث أحد أىم مياحث علم أصوؿ الفقرو، كىو ميحث الاجتهاد بُ العلة، كذلك بيحثو عند الإما الغزالر، كىل امتاز عن غتَه بُ درسو إياه، كىذا ما جعلتٍ أيرح الاشكاؿ التالر: كيف أجتهد الإما الغزالر بُ العلة؟. ككاف من أىم تطلعات الدراسة بياف مراتب الاجتهاد بُ العلة، ككذا ىل للئما الغزالر أثر بُ إثراء ىذا ات١وضوع. كللئجابة عن ىذا السؤاؿ اشتملت ات١ذكرة على: مقردمة كفصلتُ، الفصل الأكؿ احتول ترتٚة للئما الغزالر، ككذا التعريف بالاجتهاد كالعلة كله على حدة، أما الفصل الثاني فقرد تضمن اتٟديث عن مراتب الاجتهاد بُ العلة كل مرتيةبُ ميحث مستقرل، بداية بتحقريق ات١ناط بٍ التنقريح كأخ ن تَا تٗريج ات١ناط، كخات٘ة. الكلمات المفتاحية: الاجتهاد- العلة- تٖقريق ات١ناط- تنقريح ات١ناط- تٗريج ات١ناط- الغزالر. Summary of the memoir: This research discusses one of the most important researches of the science of jurisprudence, the Ijtihad in The Cause , through this research with Imam Al- Ghazali, and whether he is better than others in his study of it, which made me ask the following question: How did Imam Al-Ghazali ijtahad in the cause?. One of the most important aspirations of the study was to show the lev els of Ijtihad in the cause, as well as whether Imam Al- Ghazali enriched this topic. To answer this question, the memore included: An Introduction and t wo chapters. Chapter I included a translation by Imam Al- Ghazali, as well as the definition of Ijtihad and the cause each by itself. Chapter II included the discussion of the ranks of ijtihad in the Cause, each rank in an independent investigation, starting with the achievement of Manaat, then the Refining, and finally Showing the Manaat, and a conclusion Keywords: Ijtihad, Cause, Achieving Al Manaat, Refining Al Manaat, Showing Al Manaat, Al-Ghazali.